Psychological resilience trajectories after the COVID-19 pandemic: the role of lifestyle and psychosocial factors in a cohort at increased alzheimer’s disease risk - Contador, Israel; Akinci, Müge; Palpatzis, Eleni; Aguilar-Domínguez, Pablo; Deulofeu, Carme; Fuentes-Julian, Sherezade; Fauria, Karine; Minguillón, Carolina; Grau-Rivera, Oriol; Sánchez-Benavides, Gonzalo; Arenaza-Urquijo, Eider M.; Anastasi, Federica; et al. (Social Psychiatry and Psychiatric Epidemiology, 2025)
This longitudinal cohort study evaluates whether lifestyle and psychosocial factors are associated with psychological resilience at two time points of COVID-19 pandemic. Moreover, we investigated the mediating role of perceived stress on these associations. A total of 677 cognitively unimpaired (CU) older adults at increased risk of Alzheimer's disease (AD) completed the Hospital Anxiety and Depression Scale (HADS). Based on the Reliable Change Index (RCI), HADS trajectories were defined at two intervals: (1) pre-pandemic-confinement (follow-up = 2,28 ± 0,84 years); (2) confinement-post-confinement (follow-up = 1,49 ± 0,12 years). Then, 4 trajectory groups were defined: Psychological Resilience (n = 448, stable or improve at both intervals), Descending (n = 84, stable/improve [interval 1]-worsen [interval 2]), Recovery (n = 59, worsening [interval 1], improvement [interval 2] ) and Non-resilient (n = 86, worsening at both intervals). Logistic regression models (LRM) were applied considering lifestyle (physical and leisure activities, sleep) and psychosocial factors (social relationships and emotional support) as predictors of psychological resilience trajectory (i.e., outcome) at both intervals. Finally, mediation analyses were carried out to test the effect of perceived stress on the relationships between the predictive factors and psychological resilience. Our finding showed that most participants followed a psychological resilient trajectory (66,1%). LRMs indicated that higher physical activity level, a greater number of social interactions and longer sleep duration were significantly associated with a psychological resilience trajectory both at confinement and at the 1.5 years follow-up. Lastly, the mediation analyses suggested that these factors influence psychological resilience through the mitigation of perceived stress. These findings underscore the role of physical activity, social interactions and sleep quality to strengthen individuals' capacity to cope with stress during prolonged crisis such as the COVID-19 pandemic. These lifestyle and psychological factors may be valuable targets for public health strategies aimed to prevent mental health problems.